The legal security of business in Ukraine - Беззубов, Дмитро Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In the article the problem of security of business as the subject of economic relations. Analyzes the legal and economic components of the category of security. Identify areas of software security. A systematization security areas of business. The analysis of these components of enterprise security: financial security, economic security, legal safety. Identify areas of business security by components of economic activity. Safety analyzes components of economic activity: political, international, legal and economic. In terms of performance defined areas of business security. Analyzes the security regulations of business: laws of Ukraine, the Cabinet of Ministers of Ukraine, subordinate legislation. Structured security features of business as an entity and legal entity. Establish lines of improving the safety of business.